2013
DOI: 10.1021/ef401150w
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Water Desulfurization of Organic Sulfides Is Consistent with Free-Radical Kinetics

Abstract: Supercritical water desulfurization (SCWDS) has potential as a technique for removing sulfur from feedstocks such as heavy oil and bitumen. However, a fundamental understanding of SCWDS (such as the underlying chemical mechanisms, relative rates of desulfurization, and the role of SCW and hydrocarbons) is limited. In the present work, we have gained molecular-level insights into this process by measuring the kinetics of decomposition of a variety of organic sulfides in the presence of hydrocarbons and supercri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 43 publications
4
81
0
Order By: Relevance
“…It is well known that the combustion of hydrocarbon compounds containing N or S will release a great deal of air pollutants (NOx, SOx) [12,94], whereas the existence of Ni and V in heavy oil will enhance the viscosity of crude oil and deactivate the cracking catalyst. In addition, the Ni and V in refined oil will accelerate the wearing and corrosion of the turbo wall and the continuous emission of their oxidation have potential carcinogenic risk [95][96][97].…”
Section: Removals Of Heteroatomsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that the combustion of hydrocarbon compounds containing N or S will release a great deal of air pollutants (NOx, SOx) [12,94], whereas the existence of Ni and V in heavy oil will enhance the viscosity of crude oil and deactivate the cracking catalyst. In addition, the Ni and V in refined oil will accelerate the wearing and corrosion of the turbo wall and the continuous emission of their oxidation have potential carcinogenic risk [95][96][97].…”
Section: Removals Of Heteroatomsmentioning
confidence: 99%
“…Extensive studies showed that the introduction of SCW could effectively lower the sulfur content of heavy oil [12,59,75,100]. However, it is noteworthy that the removal of sulfur was closely related to the location of sulfur in compounds [12,94]. Usually, the aliphatic sulfur (in mercaptanes, sulfides and disulfides) cleaves easily in SCW, while the aromatic sulfur (in thiophene) is difficult to be reduced because of their steric hindrance [12,94,101].…”
Section: Removal Of Sulfurmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of oxygen in CO 2 corresponds to 50.3 wt.% of oxygen in OM. Hydrogen sulfide appeared in the conversion products of OM supplied from II fuel cylinder (Sample 2, Table 2) as a result of thermolysis and hydrolysis of the aliphatic C S bonds [33,34]. Approximately as little as 3% of sulfur from initial COM evolved as H 2 S because the bulk of COM sulfur is located in the composition of thiophene-like structural fragments.…”
Section: The First Stage Of Scw Conversion Of Brown Coalmentioning
confidence: 99%
“…The decomposition rates of the aliphatic and aromatic sulfides varied depending on their molecular structure, with conversions after 31 min at 400°C ranging from less than 3 % to more than 90 % (Patwardhan et al 2013). Supercritical water upgrading (SCWU) of crude oils reduces sulfur content and decreases average molecular weight, without rejecting carbon as coke products.…”
Section: Sulfur Removal From Petroleummentioning
confidence: 99%